Eksplorasi Unsur Matematika dalam Kebudayaan Masyarakat Jawa - Dedy Yusuf Aditya (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2017)
This study aims to determine the content of elements of mathematics in the culture of Java society, especially Central Java. The research method used is explorative survey method with the qualitative approach. Data collection was done by triangulation ie interview, observation, and literature study. The conclusion obtained is that there are two elements of mathematics in the determination of good days of traditional ceremony “mantu” or wedding such as elements of fact mathematics and the element of time.